Quality of life and pain severity changes over time in patients with breast cancer who were referred for palliative oncology treatment in Indonesia: a hospital-based cohort study - Gayatri, Dwi; Efremov, Ljupcho; Wienke, Andreas; Mikolajczyk, Rafael; Kantelhardt, Eva J. (Frontiers in Global Women's Health, 2025)
IntroductionUnderstanding quality of life (QOL) and changes in pain severity over time is important to quantify cancer patients' treatment outcomes. However, this information is limited, especially in lower-middle-income countries. This study aimed to prospectively assess QOL, QOL domains, and pain severity over time in patients with advanced breast cancer in Indonesia.MethodsWomen with advanced breast cancer (n = 160) who were referred to the palliative oncology unit were enrolled in the study. They completed the European Organization for Research and Treatment of Cancer QOL Questionnaire for advanced cancer patients (EORTC QLQ-C15-PAL) and the visual analog scale (VAS) for pain severity at three assessment points, namely, at baseline (T0) and at 3- (T1) and 6-month (T2) follow-ups. The repeated-measures analysis of variance model was used to assess changes over time after adjusting for age, place of residence, marital status, and Karnofsky Performance Status score. Change over time was classified into three groups, namely, deterioration, improvement, or a small difference.ResultsThe descriptive analysis showed that the patients’ EORTC QLQ-C15-PAL mean scores for overall QOL and the functional scales (physical and emotional functioning) were fair to good at all assessment points (range: 60–70 points) and substantially better at T0 compared to T1 and T2. In addition, most of the scores for the symptom scales of the EORTC QLQ-C15-PAL indicated lessening symptom burden (<10 points), except for pain and fatigue (20–30 points). At the same time, overall QOL, emotional functioning, fatigue, dyspnea, appetite loss, constipation, and VAS score remained stable over time. Exceptions were found for physical functioning (a medium to large deterioration with scores of −16.5 and −19.8 points, respectively) and insomnia (a medium improvement with a score of −13.4 points), with clinically relevant changes.ConclusionsOur findings from a 6-month longitudinal study show that palliative oncology treatment benefitted patients with advanced breast cancer in this health facility across several symptom scales.